2019
DOI: 10.1088/1755-1315/372/1/012036
|View full text |Cite
|
Sign up to set email alerts
|

Texture Profile and Sensory Characteristics of Kefir with Colostrum Addition

Abstract: This study aims at knowing the effect of using raw material combination (cow milk and colostrum) in making kefir on texture profile and sensory characteristics. This study used 6 combinations of treatment; P1 = 100 % cow milk; P2 = 80 % cow milk + 20 % colostrum; P3 = 60 % cow milk + 20 % colostrum; P4 = 40 % cow milk + 60 % colostrum; P5 = 20 % cow milk + 80 % colostrum and P6 = 100 % colostrum. The result shows that hardness and cohesiveness were not influenced by the combination of raw material, gumminess h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The lowest shear stress value was measured for the control sample and the highest shear stress value was measured in the case of 1.5 U/g protein MTGase concentrations. A study by [10] reported similar results in the case of kefirs made from cow milk with different MTGase concentrations. It was found that a higher MTGase concentration increased the viscosity of samples.…”
Section: Gel Firmness Of the Final Kefir Productssupporting
confidence: 57%
See 3 more Smart Citations
“…The lowest shear stress value was measured for the control sample and the highest shear stress value was measured in the case of 1.5 U/g protein MTGase concentrations. A study by [10] reported similar results in the case of kefirs made from cow milk with different MTGase concentrations. It was found that a higher MTGase concentration increased the viscosity of samples.…”
Section: Gel Firmness Of the Final Kefir Productssupporting
confidence: 57%
“…This was also clearly reflected by results of kefir made with donkey milk (fat 1.02 ± 0.014) as compared with cow milk (1.26 ± 0.17) or goat milk (1.34 ± 0.02), both of which resulted in less whey loss (see on Figure 3) due to their higher initial milk fat level. 2), cow kefir with 0.5 U/g protein MTGase (3), cow kefir with 1 U/g protein MTGase (4), cow kefir with 1.5 U/g protein MTGase ( 5); (6-9) control ( 6), goat kefir with 0.5 U/g protein MTGase (7), goat kefir with 1 U/g protein MTGase (8), goat kefir with 1.5 U/g protein MTGase ( 9); (10-13) control (10), donkey kefir with 0.5 U/g protein MTGase (11), donkey kefir with 1 U/g protein MTGase (12), donkey kefir with 1.5 U/g protein MTGase (13).…”
Section: Physical-chemical Quality Characteristics Of the Final Kefir Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing the concentration of secang wood extract added to goat milk resulted in an increase in the pH value and a decrease in the acidity of the resulting kefir (Tabel 3), thus, decreasing the consistency of kefir. A previous study reported that raw materials and ingredients influenced the product's texture (Setyawardani et al, 2019). Statistical analysis showed that goat-milk kefir with the addition of secang wood extract showed an effect on the taste (p<0.05).…”
Section: The Sensory Attributes Qualitymentioning
confidence: 91%